2011
DOI: 10.1002/art.30455
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor FBI‐1/OCZF/LRF is expressed in osteoclasts and regulates RANKL‐induced osteoclast formation in vitro and in vivo

Abstract: Objective. Since transcription factors expressed in osteoclasts are possible targets for regulation of bone destruction in bone disorders, we investigated the expression of the transcription factor FBI-1/OCZF/LRF (in humans, factor that binds to inducer of short transcripts of human immunodeficiency virus type 1; in rats, osteoclast-derived zinc finger; in mice, leukemia/ lymphoma-related factor) in patients with rheumatoid arthritis (RA), and assessed its role in osteoclastogenesis in vivo.Methods. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…[17][18][19] Bone marrow cells were obtained from the tibia and femur of 4-6-week-old male SD rats or 5-week-old female C57BL/6 mouse. Rat bone marrow cells were cultured in 24-well plates (1 Â 10 6 cells per well) in a-MEM (Gibco, Grand Island, NY, USA) containing 15% FBS (Biosource, Rockville, MD, USA) in the presence of 10 À 8 M 1a,25(OH) 2 D 3 , 20 ng/ml of RANKL, and 10% heat-treated ROS17/2.8 cell-conditioned medium (htROSCM).…”
Section: Osteoclast Differentiationmentioning
confidence: 99%
“…[17][18][19] Bone marrow cells were obtained from the tibia and femur of 4-6-week-old male SD rats or 5-week-old female C57BL/6 mouse. Rat bone marrow cells were cultured in 24-well plates (1 Â 10 6 cells per well) in a-MEM (Gibco, Grand Island, NY, USA) containing 15% FBS (Biosource, Rockville, MD, USA) in the presence of 10 À 8 M 1a,25(OH) 2 D 3 , 20 ng/ml of RANKL, and 10% heat-treated ROS17/2.8 cell-conditioned medium (htROSCM).…”
Section: Osteoclast Differentiationmentioning
confidence: 99%
“…55 In a follow-up publication, Kukita and colleagues finely described the function of LRF in osteoclastogenesis. 63 Taking advantage of a previous analysis of a transgenic mouse model overexpressing LRF in osteoclast progenitors under the Ctsk gene promoter, these authors linked the high levels of LRF to fragile bones and significantly lower bone mineral content and bone mineral density, as well as to a marked increase in the number of osteoclasts, but not osteoblasts. 63 Mechanistically, Kukita and colleagues defined LRF as a positively regulated downstream target gene of RANKL signaling that is essential to the elevation of levels of NFATc1.…”
Section: Osteoclastsmentioning
confidence: 99%
“…63 Taking advantage of a previous analysis of a transgenic mouse model overexpressing LRF in osteoclast progenitors under the Ctsk gene promoter, these authors linked the high levels of LRF to fragile bones and significantly lower bone mineral content and bone mineral density, as well as to a marked increase in the number of osteoclasts, but not osteoblasts. 63 Mechanistically, Kukita and colleagues defined LRF as a positively regulated downstream target gene of RANKL signaling that is essential to the elevation of levels of NFATc1. Interestingly, they also showed that LRF decreases p21 expression in precursor cells but increases expression of p21 and p27 in osteoclasts, suggesting different roles for LRF in proliferating osteoclast precursors and mature osteoclasts.…”
Section: Osteoclastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mice overexpressing LRF in osteoclasts were shown to exhibit an osteoporotic phenotype due to the increased number of osteoclasts (24). However, the physiological function of LRF in bone remodeling has not been demonstrated, because global deletion of LRF results in embryonic lethality (14).…”
mentioning
confidence: 99%